2009
DOI: 10.2113/gsecongeo.104.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Fixation within Mine Wastes of Ultramafic-Hosted Ore Deposits: Examples from the Clinton Creek and Cassiar Chrysotile Deposits, Canada

Abstract: Carbon dioxide (CO2) is sequestered through the weathering and subsequent mineralization of the chrysotile mine tailings at Clinton Creek, Yukon Territory, and Cassiar, British Columbia, Canada. Accelerated weathering is attributed to a dramatic increase in surface area, which occurs during the milling of ore. We provide a detailed account of the natural process of carbon trapping and storage as it occurs at Clinton Creek and Cassiar, including mineralogy, modes of occurrence, methods of formation for carbonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
217
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 227 publications
(222 citation statements)
references
References 58 publications
5
217
0
Order By: Relevance
“…In addition, both subaerial and seafloor ultramafic rocks are known to take up significant CO 2 in secondary alteration minerals (e.g. ; ; Trommsdorff and Evans, 1977;Trommsdorff et al, 1980;Ferry, 1995;Surour and Arafa, 1997;Kelley et al, 2001;Fr h-Green et al, 2003;Ludwig et al, 2006;2011;Wilson et al, 2006Wilson et al, , 2009aWilson et al, , 2009b; ; . Therefore, even though ultramafic rocks are less abundant than other types of silicate rocks on Earth's surface, the influence of ultramafic rocks on the carbon cycle may nonetheless be important.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, both subaerial and seafloor ultramafic rocks are known to take up significant CO 2 in secondary alteration minerals (e.g. ; ; Trommsdorff and Evans, 1977;Trommsdorff et al, 1980;Ferry, 1995;Surour and Arafa, 1997;Kelley et al, 2001;Fr h-Green et al, 2003;Ludwig et al, 2006;2011;Wilson et al, 2006Wilson et al, , 2009aWilson et al, , 2009b; ; . Therefore, even though ultramafic rocks are less abundant than other types of silicate rocks on Earth's surface, the influence of ultramafic rocks on the carbon cycle may nonetheless be important.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Brenker et al, 2007;Dasgupta and Hirschmann, 2010) while only a few studies have investigated rates of CO 2 uptake during weathering of ultramafic rocks (e.g. Wilson et al, 2006Wilson et al, , 2009aWilson et al, , 2009b. Wilson et al (2006Wilson et al ( , 2009aWilson et al ( , 2009b) investigated active carbonation of kimberlite diamond mine tailings in northern Canada and demonstrated that these mine tailings sequester on the order of 106 kg C0 2 /yr for each mine.…”
Section: ;mentioning
confidence: 99%
See 1 more Smart Citation
“…Wilson et al (2009) offsetting some of the greenhouse gas emissions associated with mining activities. The nature of the host species that bind carbon crystallographically was critical for assessing the amount of stored CO 2 in that study, since gangue minerals (e.g., magnesite) and surface precipitates (e.g., hydromagnesite) play different roles and must be distinguished.…”
Section: Im P L I C a T I O N S F O R C A R B O N S E Q U E S T R A Tmentioning
confidence: 99%
“…Conversely, the exchange of Cl for CO 3 could fix in excess of 40 000 metric tons CO 2 per year, if end-member iowaite is reacted to form pyaroaurite. Total greenhouse gas emissions at Mount Keith are approximately 350 000 metric tons CO 2 equivalent (Wilson et al 2009). Careful stewardship of anion exchange reactions in hydrotalcite group minerals could, thus, substantially impact the greenhouse gas emissions of mine operations.…”
Section: Im P L I C a T I O N S F O R C A R B O N S E Q U E S T R A Tmentioning
confidence: 99%